AR Module Development for Reading Comprehension: An Ethno-Meaningful Learning Needs Analysis - Atika Zikri; Afnita Afnita; Syahrul Ramadhan; Nursaid Nursaid (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Indonesian students’ reading comprehension proficiency remains a critical challenge, as evidenced by Indonesia’s ranking of 71st among 81 participating countries and economies in PISA 2022, with a reading score of 359, substantially below the OECD average. Objective: This study presents a needs analysis as the foundational phase in developing an interactive augmented reality (AR) module based on Ethno-Meaningful Learning to improve senior high school students’ reading comprehension of observation report texts. Methods: Using a descriptive qualitative approach, data were collected through questionnaires, interviews, and document analysis involving nine Indonesian language teachers and 34 students at SMA Pembangunan Padang. Results: The results reveal significant gaps between current learning conditions and ideal learning requirements: (1) 88.9% of teachers still rely on conventional, text-based instruction; (2) 82.5% of students find reading lessons unmotivating; (3) 94.1% of students have never experienced AR-based learning; and (4) 100% of teachers confirmed the absence of interactive digital modules integrating local Minangkabau culture. A gap analysis across five dimensions (methods, media, content, technology, and literacy) confirms the urgent need for an innovative, culturally grounded, and technology-enabled learning solution. Conclusion: These findings substantiate the need to develop an interactive AR-based module that integrates Ethno-Meaningful Learning principles to enhance students’ literal, inferential, and critical comprehension of observation report texts. This study contributes a culturally grounded and empirically validated framework for developing AR-based reading modules, thereby advancing the integration of ethnopedagogy and educational technology into Indonesian language instruction.